Three KINSSHIP syndrome patients with mosaic and germline AFF3 variants. Issue 5 (7th January 2023) - Inoue, Yuta; Tsuchida, Naomi; Okamoto, Nobuhiko; Shuichi, Shimakawa; Ohashi, Kei; Saitoh, Shinji; Ogawa, Atsushi; Hamada, Keisuke; Sakamoto, Masamune; Miyake, Noriko; Hamanaka, Kohei; Fujita, Atsushi; et al.
Abstract: AFF3 at 2q11.2 encodes the nuclear transcriptional activator AF4/FMR2 Family Member 3. AFF3 constitutes super elongation complex like 3, which plays a role in promoting the expression of genes involved in neurogenesis and development. The degron motif in AFF3 with nine highly conserved amino acids is recognized by E3 ubiquitin ligase to induce protein degradation. Recently, AFF3 missense variants in this region and variants featuring deletion including this region were identified and shown to cause KINSSHIP syndrome. In this study, we identified two novel and one previously reported missense variants in the degron of AFF3 in three unrelated Japanese patients. Notably, two of these three variants exhibited mosaicism in the examined tissues. This study suggests that mosaic variants also cause KINSSHIP syndrome, showing various phenotypes. Abstract :